General versus regional anaesthesia for caesarean section indicated for acute foetal distress: a retrospective cohort study - Junette Arlette Mbengono Metogo (BMC Anesthesiology, 2021)
Abstract Background Acute foetal distress (AFD) is a life-threatening foetal condition complicating 2% of all pregnancies and accounting for 8.9% of caesarean sections (CS) especially in developing nations. Despite the severity of the problem, no evidence exists as to the safest anaesthetic technique for the mother and foetus couple undergoing CS for AFD. We aimed to compare general anaesthesia (GA) versus regional (spinal and epidural) anaesthesia in terms of their perioperative maternal and foetal outcomes. Methods We carried out a retrospective cohort study by reviewing the medical records of all women who underwent CS indicated for AFD between 2015 to 2018 at the Douala General Hospital, Cameroon. Medical records of neonates were also reviewed. We sought to investigate the association between GA, and regional anaesthesia administered during CS for AFD and foetal and maternal outcomes. The threshold of statistical significance was set at 0.05. Results We enrolled the medical records of 117 pregnant women who underwent CS indicated for AFD. Their mean age and mean gestational age were 30.5 ± 4.8 years and 40 weeks respectively. Eighty-three (70.9%), 29 (24.8%) and 05 (4.3%) pregnant women underwent CS under SA, GA and EA respectively. Neonates delivered by CS under GA were more likely to have a significantly low APGAR score at both the 1st (RR = 1.93, p = 0.014) and third-minute (RR = 2.52, p = 0.012) and to be resuscitated at birth (RR = 2.15, p = 0.015). Past CS, FHR pattern on CTG didn’t affect these results in multivariate analysis. Adverse maternal outcomes are shown to be higher following SA when compared to GA. Conclusion The study infers an association between CS performed for AFD under GA and foetal morbidity. This, however, failed to translate into a difference in perinatal mortality when comparing GA vs RA. This finding does not discount the role of GA, but we emphasize the need for specific precautions like adequate anticipation for neonatal resuscitation to reduce neonatal complications associated with CS performed for AFD under GA.